Transposon activity and nucleotide triplet instability: new perspectives on their potential interplay in brain disorders - Pepe, Giuseppe; Storto, Marianna; Di Pardo, Alba; Maglione, Vittorio (Frontiers in Neuroscience, 2025)
Genomic instability is a key feature of many neurological disorders, with transposon activation and nucleotide triplet repeat instability playing critical roles. Transposons, which are also referred to as mobile genetic elements, have the potential to destabilize the genome and interfere with gene expression. Conversely, changes in nucleotide triplet sequences, such as expansions or contractions, can lead to the production of abnormal proteins or nonfunctional RNAs. In this perspective, we discussed the intricate relationship between these two forms of genomic instability and their influence on brain disorders. We analyzed the molecular mechanisms that contribute to these phenomena, the shared regulatory systems that govern them, and their role in neurological conditions. Additionally, we provided some insights into the development of potential therapies for brain disorders linked to these genomic alterations.